RISK MANAGEMENT ANALYSIS ON THE CAR DRIVERS IN INDONESIA - Hendro Kuntohadi; Yosi Pahala; Rohana Sitanggang (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
Car drivers in Indonesia will always face many kinds of risks. This research contains the context determination of this research, identifies all the significant risks, measures the frequency and impact of all the risks, draws all the identified risks in the chart, and describes how to manage or mitigate the risks. The dangerous risks which have high frequency and high impact are: 1) Many car drivers get the driving license without taking a driving course and without learning carefully the theory of driving a car; 2) Many car drivers get the driving license through illegal procedure; 3) Many car manufacturers eliminate some car safety equipment to lower the sales price; 4) The ingredients of the gasoline cannot fulfill/match the need of the car (e.g. RON number); 5) In some places the traffic is too crowded; 6) Many damaged roads may cause accidents; 7) Many roads and transportation modes cannot fulfill the demands of transportation. The recommendation (mitigation) for Risk Controlling is that all stakeholders (legislative, executive, judicative, manufacturers, people, car drivers, schools and universities, researchers,  etc)  should  obey  the  regulations,  moral,  ethics  for  car  riders.  It  is mandatory that every candidate of car driver take a course in a certified car driving ourse. Police should arrange a complete and comprehensive reference book for car driver candidates to get a driving license.